2018
DOI: 10.1021/acs.iecr.7b05281
|View full text |Cite
|
Sign up to set email alerts
|

Cold Wall Chemical Vapor Deposition Graphene-Based Conductive Tunable Film Barrier

Abstract: In this paper, we report on a continuous, flexible, and transparent graphene film obtained by cold wall chemical vapor deposition (CVD) on Cu foil. The good continuity of the graphene film, obtained in optimized conditions (e.g., pretreatment to increase copper grain size, Ar flow during synthesis to control Cu sublimation) was successfully transferred on a PET substrate to be applied with a double function of window electrode and barrier film. PET film after a single layer graphene deposition showed good perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 96 publications
1
13
0
Order By: Relevance
“…Optimizing the synthesis conditions of cold wall CVD, such as pretreatment and controllable Ar flow, enables to prepare a continuous flexible G‐TCFs on PET . PET film with the single layer graphene deposition shows a sheet resistance of 0.6 Ω sq −1 at 550 nm, 95% reduction of the oxygen barrier properties, and ∼96% reduction of water vapor transmission rate.…”
Section: Graphenementioning
confidence: 99%
“…Optimizing the synthesis conditions of cold wall CVD, such as pretreatment and controllable Ar flow, enables to prepare a continuous flexible G‐TCFs on PET . PET film with the single layer graphene deposition shows a sheet resistance of 0.6 Ω sq −1 at 550 nm, 95% reduction of the oxygen barrier properties, and ∼96% reduction of water vapor transmission rate.…”
Section: Graphenementioning
confidence: 99%
“…32 The intensity and position of the 2D peak can be used to identify the quality and thickness of graphene samples. 33 The absence of the D peak from the prole of the 3DGNs implies its high quality ( Fig. 3), which is further conrmed by the 2D peak (the intensity of 2D peak is much higher than that of the RGO sample).…”
Section: Resultsmentioning
confidence: 96%
“…Raman spectroscopy is a useful, non-destructive tool to obtain information such as thickness, quality and average size of the graphite-like materials, making it one of the most popular methods to analyze graphene samples. [31][32][33] There are three major signals can be seen: G, D and 2D peaks. The G peak is associated with the E 2g phonon at the Brillouin zone center and produces a signal at $1580 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The cold wall CVD method has some critical advantages over the hot wall approach, namely a less sophisticated design of the reactor, a relatively short deposition time of only a few minutes, a rapid sample heating time, and a rapid sample cooling time [ 24 , 81 , 82 ]. Faster heating and cooling are beneficial for achieving fast growth of graphene, which means significantly reduced costs associated with maintaining process conditions (pressure, temperature and hydrogen flow) [ 83 ].…”
Section: Chemical Vapour Depositionmentioning
confidence: 99%
“…proposed cold wall CVD technique is the significantly reduced energy costs due to much shorter synthesis times (6−12 min) and low vacuum conditions (1.1 × 10 −2 bar)[83]. Chang et al demonstrated the feasibility of a resistively heated stage (pyrolytic graphite/pyrolytic boron nitride) cold wall CVD for the synthesis of single-layer and few-layer graphene sheets on Ar plasma treated Cu and Ni foils using CH4 as a gaseous precursor.…”
mentioning
confidence: 99%